The Effect of Organizational Commitment, Organization Funding, and Intervening Organizational Performance towards Organizational Sustainability (on Islamic Boarding) - Zen, Agustian; Ali, Hapzi; Sastrodiharjo, Istianingsih; Hidayat, Wastam Wahyu (East Asian Journal of Multidisciplinary Research, 2024)
This research is expected to provide a deeper understanding of the key factors affecting the sustainability of Islamic boarding schools, as well as contribute to the development of solutions and policies that support positive and sustainable development for these institutions. This research is a research using quantitative methods, where respondents are leaders of Islamic Boarding randomly sampling from various Islamic Boarding with the number of questionnaires distributed 150 is 34 respondents. Data analysis using SPSS 25, to find whether there is an influence between organizational commitment variables and organizational sustainability, look for influences between organizational funding and organizational sustainability, and finally look for influences between organizational performance and organizational sustainability. The positive influence between the variables of Organizational Commitment has a positive and significant effect on Organizational Sustainability, so the commitment of the leaders of the Islamic Boarding School for sustainability has an influence on the Islamic Boarding School. In addition, good Organizational Funding for Islamic Boarding Schools can provide an Organizational Sustainability for Islamic Boarding Schools. Qualified Organizational Performance provides assurance for Islamic Boarding Schools to run for organizational sustainability. The results of this study provide a color, especially variables and objects of study.